Greenwashing in Sukuk Fund Allocation on the IDX: Analysis with Three Sharia ESG Discrepancy Indicators - Magfiroh, Sayyidetul; Risnaeni, Umi suwati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the effect of greenwashing on sukuk fund allocation on the Indonesia Stock Exchange (IDX), focusing on the discrepancy between Environmental, Social, and Governance (ESG) claims and actual Sharia-compliant practices. Greenwashing, as a deceptive environmental practice, can impact Sharia investor confidence and investment fund allocation. Using multiple regression analysis, this study contributes to regulators and investors in improving Sharia ESG transparency and encouraging the development of stricter audit standards to prevent greenwashing in the Indonesian Sharia sukuk market. This study also focuses on companies operating in the mining sector.